Phenotypic characterisation of Clostridium difficile PCR ribotype 251, an emerging multi-locus sequence type clade 2 strain in Australia. (December 2019) - Hong, Stacey; Knight, Daniel R.; Chang, Barbara; Carman, Robert J.; Riley, Thomas V.
Abstract: The global emergence of epidemic Clostridium difficile PCR ribotype (RT) 027 prompted enhanced surveillance of emerging strains. Recently, there have been reports of severe C. difficile infection in Australia caused by an unusual strain of C. difficile not seen previously. Identified as PCR RT251, this strain produces toxins A (TcdA) and B (TcdB), as well as binary toxin (CDT), and shares a common phylogenetic lineage with RT027. In this study, C. difficile RT251 strains were sourced from various geographical locations and potential virulence factors were evaluated and compared to that of control strains, CD630, VPI10463 and R20291 in vitro . C. difficile RT251 strains were motile, germinated and sporulated efficiently, despite producing significantly less TcdA and TcdB compared to all control strains. Genomic analyses revealed three multi-locus sequence types (MLSTs 188, 231 and 365) with four to five loci variants compared to RT027 (ST1) all MLST clade 2. C. difficile RT251 strains were susceptible to metronidazole, vancomycin and moxifloxacin, a fluoroquinolone antimicrobial to which RT027 strains are often resistant. Further studies using whole-genome sequencing are required to determine additional virulence factors that may contribute to the pathogenicity of C. difficile RT251 strains. Highlights: Clostridium difficile PCR ribotype (RT) 251, a strain recently emerged in Australia, belongs to multi-locus sequence type (MLST) clade 2. Phenotypic characterisation assays were performed to determine virulence factors in vitro and compared with epidemic RT027, CD630 and VPI10463 strains. RT251 produced heat-resistant spores that germinated efficiently, despite being a low toxin-producer in vitro. Resistance to clindamycin and erythromycin was common in RT251 strains of ST231 lineage.